Large non-volatile tuning of magnetism mediated by electric field in Fe–Al/Pb(Mg1/3Nb2/3)O3–PbTiO3 heterostructure. (22nd May 2017) - Chen, Zhendong; Gao, Cunxu; Wei, Yanping; Zhang, Peng; Wang, Yutian; Zhang, Chao; Ma, Zhikun
Abstract: Electric-field control of magnetism is now an attractive trend to approach a new kind of fast, low-power-cost memory device. In this work, we report a strong non-volatile electric control of magnetism in an Fe–Al/Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 heterostructure. In this system, a 90° rotation of the in-plane uniaxial magnetic anisotropy is exhibited during the increase of the external electric field, which means the easy axis turns into a hard axis and the hard axis turns into an easy one. Additionally, a non-volatile switch of the remanence is observed after a sweeping of the electric field from 0 kV cm −1 to  ±  10 kV cm −1, then back to 0 kV cm −1 . More interestingly, a 20% non-volatile magnetic state tuning driven by individual pulse electric fields is shown in contrast to large tuning up to 120% caused by pulse electric fields with small assistant pulse magnetic fields, which means a 180° reverse of the magnetization. These remarkable behaviors demonstrated in this heterostructure reveal a promising potential application in magnetic memory devices mediated by electric fields.